Unusual location of primary hydatid cyst diagnosed on aspiration cytology. (13th February 2017) - Singal, Rikki; Mittal, Amit; Garg, Monika; Zaman, Muzzafar; Chaudhry, Manish; Singal, Samita; Sharma, Bhanu Pratap
Summary: Hydatid cyst (HC) is a parasitic infection caused by Echinococcus granulosus . It occurs frequently in liver and lungs. Hydatid cyst of neck is extremely rare occurrence, and here, we report it with this unusual location. A 25‐year‐old male nonhypertensive and nondiabetic presented with slowly growing painless swelling in right side of neck for 4‐5 years. The swelling measured 5 × 3 cm and was of soft to firm consistency. Fine needle aspiration cytology yielded fluid aspirate and smear showed features suggestive of HC. The intact cyst was removed surgically, and histopathological examination confirmed the diagnosis of hydatid cyst.